Analysis of cracked shear deformable plates by an effective meshfree plate formulation. (August 2015) - Tanaka, Satoyuki; Suzuki, Hirotaka; Sadamoto, Shota; Imachi, Michiya; Bui, Tinh Quoc
Highlights: We analyze cracked plate bending problems using a meshfree method. J -integral based on nodal integration is proposed. High accuracy solution is obtained using the proposed technique. Abstract: A novel technique to evaluate the path-independent integral using nodal integration is developed for cracked plate problems. The formulation is based on the Mindlin–Reissner plate theory, and the reproducing kernel is used as a meshfree interpolant. A visibility criterion, diffraction method, and enriched basis are included. To integrate the stiffness matrix, the stabilized conforming nodal integration and the sub-domain conforming integration are adopted. A moment intensity factor is also evaluated employing the J -integral based on the nodal integration. Convergence and numerical results derived from regular and irregular discretizations, node density, and other aspect ratios are analyzed.